IMPLEMENTASI DATA MINING MENGGUNAKAN ALGORITMA C4.5 UNTUK PREDIKSI EVALUASI ANGGOTA SATUAN PENGAMANAN STUDI KASUS PT. YIMM PULOGADUNG - Fery Pirmansyah; Tri Wahyudi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The inability to perform security duties is a problem that has serious consequences for both the company and the members of the security force. In today's increasingly competitive environment, where companies must search for highly competent people, a more sophisticated technical approach is needed to overcome this problem. One of the techniques used in data analysis is data mining. The researchers implemented a classification method using decision trees. Decision trees were chosen because they are one of the most used techniques in data analysis and provide rules that are easy to apply. This study uses the C4.5 algorithm to generate classification rules that decide whether a member of a security unit should be retained in a company. The results of this study showed an accuracy rate of 99.84%, demonstrating excellent ability to predict the incompetence of security unit members. Through this approach, data regarding the incompetence of security force members can be presented in a more professional and effective manner, helping companies make more informed decisions about personnel. their affairs